Decomposing the Consumption Response to Monetary Policy Shocks in Australia - Geraghty, Jessica (My University, 2022)
Does monetary policy affect households differently depending on their position on the income distribution? If so, what drives the differences? This paper attempts to answer these questions by decomposing changes in consumption following a monetary policy shock into several direct and indirect channels of transmission. Although direct channels of transmission are the most important in traditional representative agent models, the indirect channels are dominant when households are heterogeneous. Using household-level data from Australia, households are grouped into income quintiles and allowed to differ in terms of their marginal propensity to consume, their balance sheet exposures and the sensitivity of their income to economic activity. The net impact of the monetary policy shock is calculated by aggregating the changes in consumption from each of the transmission channels. An interest rate reduction stimulates the consumption of low-income earners the most, while high-income earners experience the smallest increase. This result is mostly explained by the capital gains channel, and to a lesser extent, the income channel. Changes in consumption through these indirect channels of transmission outweigh changes through the direct channels, for all income quintiles. Within quintiles, groups with sizable asset holdings such as retirees and homeowners, experience the largest changes in consumption. Though these results reflect unique aspects of the Australian context, they also align at a high level with other studies finding that expansionary monetary policy reduces inequality. More broadly, they demonstrate the importance of accounting for household heterogeneity to better understand the transmission of monetary policy and its distributional effects.
Keywords: Income, wealth and finances